Effect of FeCoNiMoW high entropy alloy binders on mechanical properties of high entropy (Ti,W,Mo,Nb,Ta)(C,N) based cermets - XIA Peng; ZHANG Houan; LIAN Jiqiong; QIAO Dongxu; TAO Xin; ZHANG Yunhao; DANG Wei; GU Siyong (Fenmo yejin jishu, 2025)
Conventional Ti(C,N)-based cermets predominantly utilize Co/Ni as the bonding phase. This study explores the preparation of high-entropy (Ti,W,Mo,Nb,Ta)(C,N)-based cermets by vacuum sintering, utilizing high-entropy (Ti,W,Mo,Nb,Ta)(C,N) ceramics as the hard phase and FeCoNiMoW high-entropy alloy as the binder phase. The effects of the sintering process and binder phase content on the microstructure and mechanical properties of the cermets were investigated. The results reveal that the cermet containing 5% FeCoNiMoW (mass fraction), sintered at 1450 ℃ for 1 h, exhibited optimal comprehensive mechanical properties with the hardness ofHV30 1844.99, traverse strength of 1430 MPa, and fracture toughness of 9.91 MPa·m1/2, respectively. These values surpass those of high-entropy cermets with a 15% Co/Ni bonding phase (mass fraction), showing increases of 14.40% in transverse strength and 5.28% in hardness. The enhancement of the mechanical properties are attributed to the larger lattice distortion effect and hysteresis diffusion effect induced by the FeCoNiMoW high-entropy alloy binder phase. Additionally, the Mo2C phase formed during the high-temperature sintering enhances the wettability between the hard phase and the binder phase. This study provides a novel strategy for developing high-strength and high-hardness Ti(C,N)-based cermets.